Zombie Art: Beyond Materialist Art Myths - Miller, Rod A. (Journal of interdisciplinary studies, 2022)
It is easy to ridicule the pretense and silliness of many works coming from the "art world." The story of the arts, for at least the past century and a half, has been one of attempts to keep alive something that is long past dead. For example, without a substantial understanding of quality, aesthetics has been held up as a substitute for life. But the aesthetic, long touted as fundamental to the goals of art, begs other questions: which aesthetic responses? What if one does not have the same, or any, aesthetic response? This essay explores an alternative, one that refutes the modernist conception of substituting mere pleasure and emotion, that is, preferences, for the idea of Beauty as the manifestation of what is known to be True and Good. Instead of seeking living art that is Beautiful, and can bring life, postmodern culture is surrounded by dead, zombie art. Strategies for stopping the flood of long-dead zombie works include reason, ridicule, and pointing the way back to Beauty.